Effects of tranexamic acid on coagulofibrinolytic markers during the early stage of severe trauma: A propensity score–matched analysis. Issue 32 (12th August 2022) - Gando, Satoshi; Shiraishi, Atsushi; Wada, Takeshi; Yamakawa, Kazuma; Fujishima, Seitaro; Saitoh, Daizoh; Kushimoto, Shigeki; Ogura, Hiroshi; Abe, Toshikazu; Mayumi, Toshihiko; Sasaki, Junichi; Kotani, Joji; et al.
Abstract : Tranexamic acid (TXA) reduces the risk of bleeding trauma death without altering the need for blood transfusion. We examined the effects of TXA on coagulation and fibrinolysis dynamics and the volume of transfusion during the early stage of trauma. This subanalysis of a prospective multicenter study of severe trauma included 276 patients divided into propensity score–matched groups with and without TXA administration. The effects of TXA on coagulation and fibrinolysis markers immediately at (time point 0) and 3 hours after (time point 3) arrival at the emergency department were investigated. The transfusion volume was determined at 24 hours after admission. TXA was administered to the patients within 3 hours (median, 64 minutes) after injury. Significant reductions in fibrin/fibrinogen degradation products and D-dimer levels from time points 0 to 3 in the TXA group compared with the non-TXA group were confirmed, with no marked differences noted in the 24-hour transfusion volumes between the 2 groups. Continuously increased levels of soluble fibrin, a marker of thrombin generation, from time points 0 to 3 and high levels of plasminogen activator inhibitor-1, a marker of inhibition of fibrinolysis, at time point 3 were observed in both groups. TXA inhibited fibrin(ogen)olysis during the early stage of severe trauma, although this was not associated with a reduction in the transfusion volume. Other confounders affecting the dynamics of fibrinolysis and transfusion requirement need to be clarified.